Firm size, technological capability, exports and economic performance: the case of electronics industry in Malaysia - Chandran, V. G. R.; Rasiah, Rajah (Journal of Business Economics and Management, 2013)
This paper examines the joint effects of technology and exports on the economic performances of electronics firms in Malaysia. The empirical results based on the Partial Least Square (PLS) estimate procedure show that technological capability plays a multiple role in that it influences both the exports and performance of a firm simultaneously. More importantly, we find evidence that exports act as a mediating variable between technological capability and firm performance. Size is found to influence all three: product capabilities, exports and firm performance but not process capabilities. This paper concludes that researchers, in future studies, need to examine the dynamism between size, technology, exports and performance.